Interspecies Communication between Pathogens and Immune Cells via Bacterial Membrane Vesicles - Jurkoshek, Katerina S.; Wang, Ying; Athman, Jaffre J.; Barton, Marian R.; Wearsch, Pamela A. (Frontiers in Cell and Developmental Biology, 2016)
The production of extracellular vesicles is a universal mechanism for intercellular communication that is conserved across kingdoms. Prokaryotes secrete 50–250 nm membrane vesicles (MVs) in a manner that is regulated by environmental stress and is thought to promote survival. Since many types of host-derived stress are encountered during infection, this implies an important role for MV secretion in bacterial pathogenesis. Accordingly, MVs produced by gram-positive and gram-negative pathogens contain toxins, virulence factors, and other molecules that promote survival in the host. However, recent studies have also shown that bacterial MVs are enriched for molecules that stimulate innate and adaptive immune responses. As an example, MVs may serve multiple, important roles in regulating the host response to Mycobacterium tuberculosis (Mtb), an intracellular pathogen that infects lung macrophages and resides within modified phagosomes. Previously, we demonstrated that Mtb secretes MVs during infection that may regulate infected and uninfected immune cells. Our present data demonstrates that Mtb MVs inhibit the functions of macrophages and T cells, but promote MHC-II antigen presentation by dendritic cells. We conclude that bacterial MVs serve dual and opposing roles in the activation of and defense against host immune responses to Mtb and other bacterial pathogens. We also propose that MV secretion is a central mechanism for interspecies communication between bacteria and host cells during infection.